The Development of Student Soft Skills through the Integration of PJBL STEAM Learning in The Organic Chemistry 1 Topic of Hydrocarbons - Handayani, Dewi; Nurhamidah, Nurhamidah (Jurnal Pendidikan Kimia Indonesia, 2024)
This research aims to improve students' soft skills in facing the 21st century, making learning more interesting and enjoyable so that the quality of human resources becomes better. This study explores how integrating Project-Based Learning (PjBL) with the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach can improve students' soft skills in Organic Chemistry 1, specifically focusing on the topic of hydrocarbons. The research subjects were students taking Organic Chemistry 1 courses in the odd semester of the 2022/2023 academic year. This type of research is qualitative research with data collection techniques in the form of interviews, field observations, and reflective journals. The STEAM approach, encompassing Science, Technology, Engineering, Art, and Mathematics, is implemented through a six-stage learning process, namely providing essential questions, making a project plan, preparing a project schedule, monitoring students and project progress, assessing/testing results, and providing student experience. The research results show that students like project learning using the STEAM approach with an average questionnaire response result of 89.14% with very good criteria. 36% of students experienced problems when making project planning assignments in finding interesting ideas related to organic chemistry 1 material using the STEAM approach. The integration of STEAM in project-based learning can develop students' soft skills.